Profile of psychology Professionals in the South of the State of Maranhão (Research, Society and Development, 2022)
The study sought to identify the professional profile of psychologists who work in the south of the state of Maranhão. The objective was to trace sociodemographic characteristics, education and professional performance. An online questionnaire containing 30 questions was used between September and November 2019 with professionals registered in the CRP-22. The results corroborate the existing literature on the profile of psychologists: young professionals, predominance of the female sex, diversified performance, predominance of clinical activity, with a postgraduate degree and more than one contractual relationship, public and private sector. The results indicate that Psychology is on the rise in the region, requiring professional improvement to meet regional demands.